THE EFFECT OF SERVICE QUALITY AND PRICE ON CONSUMER LOYALTY IN USING GO-JEK SERVICES: (A study of Go-Jek application users in Medan City) - Situmorang, Reynaldy; Mardhiyah, Ainun (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study aims to analyze how the influence of service quality and price on consumer loyalty in using Go-Jek services (Study on consumers in Medan City using the Go-Jek application). The effect of the related variables, namely service quality and price, will be carried out partially and simultaneously on increasing consumer loyalty. This research uses quantitative research with an associative approach. Sampling using purposive sampling technique using 100 respondents as the research sample. Primary data in this study was obtained from distributing questionnaires through google form, and secondary data obtained through literature study. The analytical method used is validity test, classical assumption test, reliability test, multiple linear regression analysis and hypothesis testing. The results showed that the service quality variable (X1) and the price variable (X2) partially had a significant effect on consumer loyalty (Y). Based on the coefficient of determination test, the R2 value is 0.441, which means the influence of service quality and price on consumer loyalty in using Go-Jek services in Medan City is 44.1% while the remaining 54.9% is influenced by other factors beyond this study.